Design Principles for Heteroatom-Doped Nanocarbon to Achieve Strong Anchoring of Polysulfides for Lithium-Sulfur Batteries - Hou, Ting-Zheng; Chen, Xiang; Peng, Hong-Jie; Huang, Jia-Qi; Li, Bo-Quan; Zhang, Qiang; Li, Bo (Small (Weinheim an der Bergstrasse, Germany), 2016)
Lithium–sulfur (Li–S) batteries have been intensively concerned to fulfill the urgent demands of high capacity energy storage. One of the major unsolved issues is the complex diffusion of lithium polysulfide intermediates, which in combination with the subsequent paradox reactions is known as the shuttle effect. Nanocarbon with homogeneous nonpolar surface served as scaffolding materials in sulfur cathode basically cannot afford a sufficient binding and confining effect to maintain lithium polysulfides within the cathode. Herein, a systematical density functional theory calculation of various heteroatoms‐doped nanocarbon materials is conducted to elaborate the mechanism and guide the future screening and rational design of Li–S cathode for better performance. It is proved that the chemical modification using N or O dopant significantly enhances the interaction between the carbon hosts and the polysulfide guests via dipole–dipole electrostatic interaction and thereby effectively prevents shuttle of polysulfides, allowing high capacity and high coulombic efficiency. By contrast, the introduction of B, F, S, P, and Cl monodopants into carbon matrix is unsatisfactory. To achieve the strong‐couple effect toward Li2Sx, the principles for rational design of doped carbon scaffolds in Li–S batteries to achieve a strong electrostatic dipole–dipole interaction are proposed. An implicit volcano plot is obtained to describe the dependence of binding energies on electronegativity of dopants. Moreover, the codoping strategy is predicted to achieve even stronger interfacial interaction to trap lithium polysulfides. Lithium–sulfur (Li–S) batteries have been intensively studied to fulfill the urgent demands of high capacity energy storage. A systematic density functional theory calculation of various heteroatoms‐doped nanocarbon materials is conducted to elaborate the mechanism and guide the future screening and rational design of Li–S cathode for better performance. While B and F doping exhibit lower Eb than undoped carbon, N and O elements offer elevated binding energies with Li2Sx that form a strong anchoring effect to alleviate shuttle effect.